Benjamin Moloise: A Freedom Fighter Poet of Soth Afriqa - Asif Ali Chatha (بازیافت)
Apartheid was a system of institutionalized racial segregation and discrimination that existed in South Africa from 1948 until the early 1990s.The system was based on white supremacy and the repression of the black majority for the benefit of the politically and economically dominant Afrikaner minority and other whites. Apartheid legislation itself was repealed in 1991 and a non-racial government was established following national elections in 1994. Benjamin Moloise was s South African poet, political activist and the follower of the then forbidden African National Congress. He was convicted to capital punishment by the apartheid regime of P.W. Botha, allegedly for murdering a policeman in 1982. He was hanged on 18 Oct 1985 at the Pretoria Central Prison despite world wide pleas for clemency. His execution by the apartheid regime led to international protests and street battles in South Africa.